Biblioanalytics: aplicação web para democratização de análises bibliométricas - Perissini, Rodrigo César (2022)
With the industrialization of science, it came to be seen as a productive and economic source, exponentially increasing the number of publications generated by scientific research and generating a need for mechanisms to facilitate its retrieval and organization as the online information sources; and also a need for mechanisms to work with this gigantic set of data, such as bibliometric tools. The problem is that the available tools have limitations that make it difficult to democratize bibliometric analyzes, especially in the Brazilian scientific field, such as the use of only the English language; financial and/or intellectual barriers, given the need to install and configure the tool, and also because some are paid; and among others. This research aims to develop a free biliometric web application with a focus on the democratization of bibliometric analysis. For the construction of BiblioAnalytics, action research was used to collect the necessary requirements within NIT/MATERIAIS, which is a group of research and development in UFSCar, and the comparison with the VantagePoint tool, when necessary, to validate the correct functioning of some of its functionalities. Finally, after the construction of BiblioAnalytics, it could be observed that the tool works even in a free environment on the web, and manages to obtain relevant and correct results, despite limitations (such as the generation of matrices for a very large set of data), providing mechanisms that contribute to the democratization of bibliometric analyzes, which means that it can be used by a much larger group of researchers and students, given that it can be accessed even by a cell phone.